Amiodarone Hepatotoxicity with Absent Phospholipidosis and Steatosis: A Case Report and Review of Amiodarone Toxicity in Various Organs - Adela Cimic; Joseph Sirintrapun (Hindawi Limited, 2013)
We present the first description of amiodarone toxicity in the liver without phospholipidosis or steatosis. In doing so, we will review the various effects of amiodarone toxicity in various organs. The patient is a young adult who had cardiac reconstruction as a child for transposition of the great vessels. A needle biopsy was taken due to elevated liver enzymes. Her ALT was 188 U/L (5-50) and AST 162 U/L (5-50). Alkaline phosphatase, total bilirubin, protein, and albumin were within normal limits. A serologic panel for viral hepatitis was negative. Antinuclear antibodies were positive at 260; however, anti-smooth muscle antibody and anti-mitochondrial antibody were negative. A protein electrophoresis showed a slightly elevated beta globulin 2 level of 0.5. Quantitative immunoglobulin levels were within normal limits except for a slightly elevated IgA 409 mg/dL (60-350). Liver ultrasound was unremarkable. The clinical differential was broad and included hepatic congestion along with autoimmune hepatitis. Sections showed only ballooned hepatocytes with Mallory-Denk bodies and perisinusoidal fibrosis. Arrival to the diagnosis was possible only after careful review of the patient's medications. After discontinuation of amiodarone, the patient's liver enzymes returned to normal levels.